Resources, Demand and Supply of Domestic Water in North Kelantan - Ibrahim, Zainuddin (2008)
Management of water resources and demand of clean water supply from the consumers have become more critical nowadays especially when there is a water quality standard to be attained. This quality standard is regulated by the government in accordance with the National Guidelines of Drinking Water Quality, which itself is based on the Guidelines of Drinking Water Quality set by WHO. As such supply of clean water by AKSB has to meet the stringent requirement at both national and international levels. The concern is to supply quality water as well as yardstick for improving our living standard and economic development. The main objectives of this study is to determine whether the demand for domestic clean water supply by AKSB is adequate and can it meet the quality requirement as stated above, in the study area in North Kelantan. The conversational per capital model of forecasting future water demand was proven not efficient; thus this study came out with new factors as independent variables. These variables are the size of household, household income and type of houses. This study will measure consumers' satisfaction with the water supply both in term of quantity and quantity in the studied area. Survey method is used to collect primary data from the respondents in the area of North Kelantan. The collected data from 504 samples were analysed using coefficient of variation to ensure reliability and quality of t1-'8 data for consumers in North Kelantan. Regression Analysis has proven that independent variables of household size and type of houses have significant effect upon consumers' satisfaction about the quality and quantity of clean water supply by AKSB. Chi square test is applied to consumers using water supply by AKSB only. Consumers using both water supply by AKSB and well water sources shows different opinion about water quality at the significant level of one percent. The results of the study proved that domestic water demand was influenced by household size and type of houses. Regression analysis also proved that household size and type of houses have significant impact upon domestic water demand. Conservation through campaign on quality water saving, using alternative water sources and recycle of water have